Is It Cost-effective to Purchase Print Books When the Equivalent E-book Is Available?. Issue 1 (2nd January 2016) - Li, Jie
ABSTRACT: The aim of this study was to analyze and compare print and electronic book usage for equivalent core clinical titles at the University of South Alabama Biomedical Library collection from 2010 to 2014 to determine format preference and if it would be necessary to purchase identical books in both electronic and print formats. The purpose of purchasing print books that are also available in electronic format is to meet the preferences of some users who prefer to read print format. Usage of 60 core books both in print and electronic formats was compared. Usage statistics were generated from the library's integrated library system for the print books—both those used in the library and checked out of the library. Electronic usage statistics of the same titles were generated from COUNTER reports; then titles in both formats were compared to determine format preference and whether it is cost-effective to purchase books in both print and electronic formats.